PENGELOLAAN DAERAH RAWAN BENCANA LAHAR PASCAERUPSI GUNUNGAPI MERAPI 2010 DI KALIPUTIH KABUPATEN MAGELANG - , rosalina kumalawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Considering impacts of lahar flood event on settlements is prerequisite in land resource best-use decision the management of susceptibility areas. This research aim to develop and analyze lahar susceptibility rate map, determine the public perception about lahar, financial valuation, and evaluation individual behavior relationship about lahar with the WTA. The advantage of this research is the government either central and local may decide policy that support management of susceptibility areas based on community by allocating their budget. Research focus was defined using purposive sampling technique. Unit of observation was villages along Kali Putih belonging to lahar-susceptible zone. The research used quantitative method, in particular multiple regression analysis. The regional mapping by hazard level was conducted by Geographical Information System (GIS). Data used in this research were primary and secondary data. Primary data were obtained by distributing questionnaire to some respondens. Sample amounts used were 1.021 respondens. Samples in risk analysis were defined using stratified sampling technique. The research theoretical contribution was to investigate behaviour mitigation according to the expected theory of utility. The research empirical contribution was to financial valuation method used towards safety and efforts to link regional characteristics, public perception about lahar, individual behavior, and also their willingness to accept. The research practical contribution was to identify management of susceptibility areas. Susceptibility analysis showed that 14.749 house unit to safe zone, 21.527 house unit to low susceptibility zone, 1.391 house unit to moderate susceptibility zone, and 4.124 house unit to high susceptibility zone. Public perception of lahar is moderate. The relationship between individual behavior and perceptions about lahar is convincing positive although the correlation is very weak. All sand material are sold and priced, it can be used to build as many as 5.138 permanent houses units. The total of houses that can be built exceeds total of houses that damaged. Lahar in these study areas can provide benefits. Results of multiple regression analysis, it can be concluded that: risk aversion, the perception of the impact of the disaster, the role of government, education level, individuals income, and dummy variables have positive effect on the WTA. Keywords: disaster, financial valuation, mitigation, perception, management